Application of Spent Li-Ion Batteries Cathode in Methylene Blue Dye Discoloration - Eric M. Garcia; Hosane A. Taroco; Ana Paula C. Madeira; Amauri G. Souza; Rafael R. A. Silva; Júlio O. F. Melo; Cristiane G. Taroco; Quele C. P. Teixeira (Journal of Chemistry)
This paper aims to present the mechanism study of methylene blue (MB) discoloration using spent Li-ion battery cathode tape and hydrogen peroxide. The recycled cathode used in this work is composed of 72% of LiCoO2, 18% of carbon, and 10% of Al. The value found for surface area is 8.9 m2/g and the ZCP value occurs in pH = 2.95. Different from what is proposed in the literature, the most likely mechanism of methylene blue discoloration is the oxidation/delitiation of LiCoO2 and the reduction of H2O2 forming OH∙. Thus, in this paper, an important and promising alternative for discoloration of textile industry dyes using spent Li-ion battery cathode is presented.